A study of common fixed points that belong to zeros of a certain given function with applications - Saleh, Hayel N.; Imdad, Mohammad; Karapinar, Erdal (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we establish some point of φ-coincidence and common φ-fixed point results for two self-mappings defined on a metric space via extended CG-simulation functions. By giving an example we show that the obtained results are a proper extension of several well-known results in the existing literature. As applications of our results, we deduce some results in partial metric spaces besides proving an existence and uniqueness result on the solution of system of integral equations.